Traumatic avulsion of extraocular muscles: case reports - Minguini,Nilza (2013)
We described the clinical, surgical details and results (motor and sensory) of the retrieving procedure of traumatically avulsed muscles in three patients with no previous history of strabismus or diplopia seen in the Department of Ophthalmology, State University of Campinas, Brazil. The slipped muscle portion was reinserted at the original insertion and under the remaining stump, which was sutured over the reinserted muscle. For all three cases there was recovery of single binocular vision and stereopsis.